The role of the built environment, food prices and neighborhood poverty in fruit and vegetable consumption: An instrumental variable analysis of the moving to opportunity experiment. (January 2021) - Colabianchi, Natalie; Antonakos, Cathy L.; Coulton, Claudia J.; Kaestner, Robert; Lauria, Mickey; Porter, Dwayne E.
Abstract: The food environment has been associated with fruit and vegetable consumption, however many studies utilize cross-sectional research designs. This study examined 3, 473 participants in the Moving to Opportunity experiment, who were randomized into groups that affected where they lived. The relationship between the built environment, food prices and neighborhood poverty, assessed over four to seven years, on fruit or vegetable consumption was examined using instrumental variable analysis. Higher food prices and neighborhood poverty were associated with lower fruit or vegetable consumption. Policies and programs that address food prices should be implemented and evaluated for their effects on fruit and vegetable consumption. Highlights: Using instrumental variable analysis, neighborhood features and diet were examined. Higher neighborhood food prices were associated with lower fruit or vegetable intake. Higher neighborhood poverty was associated with lower fruit or vegetable intake. A factor of built environment features was not related to fruit or vegetable intake.